Structural properties of graphene oxide coatings from different sheets sizes - Nurul Huda, Abu Bakar; Jamil, Ismail; K. F., Chong (Penerbitan Universiti (JAPENA), UiTM, 2019)
The structural properties of different sizes of graphene oxide (GO) sheets were observed. It is worth to mention that smaller size GO sheets (ultrasonicated 10h) exhibits higher absorption intensity, and the absorption peak was shifted towards lower wavelength (~223 nm) due to the fragmentation of the GO sheets. It has caused an extension of a π-conjugated system, thereby enhance the absorption intensity and energy. After electrophoretic deposition (EPD), the coatings exhibit a reduction in the oxygen content with oxygen-related band (ORB) values of the larger GO sheets is higher than that of small size GO sheets. The surface morphology of both the coatings are homogenous and the layers adhered well to the underlying copper. However, larger GO sheets exhibit rougher and coarser morphology than that of small size GO sheets. It is reflected in the thickness measurement where the large size GO sheets exhibit thicker film (3.16 ± 0.01 µm) while small size GO sheets possess thinner film (1.95 ± 0.02 µm).